Disseminated fusariosis with cutaneous involvement in hematologic malignancies: report of six cases with high mortality rate - Marina Zoéga Hayashida; Camila Arai Seque; Milvia Maria Simões e Silva Enokihara; Adriana Maria Porro (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Fusariosis is due to inhalation or direct contact with conidia. Clinical presentation depends on host's immunity and can be localized, focally invasive or disseminated. Given the severity of this infection and the possibility for the dermatologist to make an early diagnosis, we report six cases of patients with hematologic malignancies, who developed febrile neutropenia an skin lesions suggestive of cutaneous fusariosis. All patients had skin cultures showing growth of Fusarium solani complex, and they received amphotericin B and voriconazole. As this infection can quickly lead to death, dermatologists play a crucial role in diagnosing this disease.